Designing an Urban Environmental Management Model toward a Sustainable Global Smart City - Eliana Sari; Ananto Kusuma Seta; Dwi Atmanto; Madhakomala; Durotul Yatimah; Muhammad Mulyadi; Dwi Purwoko; Luthfi Jusniar Dwiputri; Zahra Nabilla (Jurnal Green Growth dan Manajemen Lingkungan, 2025)
This study examines the low level of adolescent participation in utilizing technology-based public services in the Special Capital Region of Jakarta (DKJ), despite the implementation of the Jakarta Smart City (JSC) initiative since 2014. Limited engagement among young citizens indicates a gap between smart city development and public education effectiveness, particularly in fostering smart people for sustainable urban governance. The study employs a Research and Development (R&D) approach based on the Gall, Gall, and Borg framework. The unit of analysis consists of adolescents aged 10–19 years residing in Pulo Gadung District, East Jakarta. A proportional random sampling technique was applied, yielding 397 respondents from a target population of 43,760 adolescents. Data were analyzed using descriptive statistics and Structural Equation Modeling (SEM) with WarpPLS to examine the relationships among smart city maturity, public education management, and adolescent participation. The study develops and validates a smart city maturity measurement instrument, a public education management instrument, and an urban environmental management model oriented toward a sustainable global smart city. Additionally, training modules and Training of Trainers (TOT) programs based on the smart people concept are produced to strengthen youth engagement. This research contributes by providing empirically grounded instruments and models to support evidence-based policies and enhance adolescent participation in smart city ecosystems.